Using songs to improve the vocabulary in the english language among sixth year students in, parallel “B” at “Daniel Rodas Bustamante public school” during the academic period 2013 – 2014 - Abad Alverca, José Jamil (2015)
This action research study was focused on the improvement of the vocabulary withthe use of songs with 24 sixth-B year students at “Daniel Rodas Bustamante” Public School. The intervention plan of six sessions was carried out to improve the vocabulary withthe use of songs. The researcher applied tests and questionnaires which were designed and used to measure the students’ progress and perception of song use. Additionally, instruments like checklists were used every session to demonstrate the students’ progress. The results indicated that the use of songsfacilitated meaningfully the improvement of the vocabulary which was reflected in the noticeable increase of the posttest scores and students’ progress during the intervention. The data received from the checklists and questionnaires also confirmed the enthusiasm and the positive attitude toward working with songs. To conclude, this study helped the students to increase their English vocabulary and the researcher, to master his teaching skills